Treatment for Post-hemorrhagic Ventricular Dilatation: A Multiple-Treatment Meta-Analysis - Mahoney, Liam; Luyt, Karen; Harding, David; Odd, David (Frontiers in Pediatrics, 2020)
Objective : To perform a systematic review and multiple treatments meta-analysis for the treatment of premature infants with post-haemorrhagic ventricular dilatation (PHVD), to prevent death or long term neuro-disability. Design/ Method: Systematic review was performed using PubMed, EMBASE and the Cochrane Library. A free-word search was performed to identify likely relevant literature intervention trials of PHVD in preterm infants. Initially network mapping was performed followed by performing a Bayesian random-effects model using the Markov chain Monte Carlo method. Areas under the cumulative ranking curve (SUCRA) was calculated as a measure of the probability that each intervention was likely to be the 1st, 2nd, 3rd (etc) best therapy. Primary outcome measure was death or moderate or severe neurodevelopmental outcome at or beyond 12 months of corrected age. Results: Ten different trials were identified, enrolling 700 individuals (449 for the primary outcome). Seven intervention categories were identified, and of the 15 possible pair-comparisons, 6 have been studied directly. In the multiple treatments meta-analysis no comparison reached conventional levels of statistical significance. Drainage Irrigation and Fibrinolytic Therapy (DRIFT) had the highest probability of being the best treatment for the primary outcome (82.1%), followed by CSF removal (10.8%), conservative management (6.7%) and then diuretic therapy (0.4%). Conclusions: PHVD is a significant cause of death and disability in developed countries, yet few therapeutic options have so far been trialled. While new therapies are urgently needed for these infants, at present NMA shows that DRIFT appears to be the most likely candidate to improve outcomes after sIVH.